Effect of different processing conditions on essential minerals and heavy metal composition of sorghum grain. Issue 1 (17th December 2020) - Mohapatra, Debabandya; Patel, Avinash Singh; Kar, Abhijit; Deshpande, Sumedha S.; Tripathi, Manoj Kumar
Abstract: A study was conducted in order to access the effect of different processing conditions on the mineral status of the grain sorghum. Whole sorghum grain was (a) cooked in excess water, (b) fermented under submerged condition, (c) steamed after fermentation, and (d) fermented, steamed, and flaked. The mineral content of the samples was determined through a microwave plasma atomic absorption spectroscope. During cooking, essential minerals like K, Fe, and Mn decreased, while Mg, Ca, and Na contents increased; while most non‐essential minerals decreased, except Ti. During fermentation Ca, Mg, and Na content increased, while heavy metals like As, Pb, Ti, and Ba decreased significantly ( p  < .05). Essential minerals like Fe and non‐essential minerals like Cr, Ni, and Al were found to be contaminated from the machine parts during processing steps like steaming and flaking. At the same time, essential minerals like K, Ca, and Mn were lost during the flaking process. Practical applications: This work provides information on how simple processing conditions like fermentation can improve the status of the essential mineral in sorghum, at the same time reducing the heavy metal presence in the sample. This study also provides an insight into where the possible metal contamination can occur during the production of fermented products and steam flaking of cereal grains like sorghum. This information will help control the metal contamination, reduction of heavy metal contamination as well as a guide for formulating the HACCP.